Assessing China's Corporate Sector Vulnerabilities - Chivakul, Mali.; Lam, Waikei (Washington, D.C. : International Monetary Fund, 2015)
This paper documents and assesses the risk stemming from rising corporate indebtedness in China using a firm-level dataset of listed firms. It finds that while leverage on average is not high, there is a fat tail of highly leveraged firms accounting for a significant share of total corporate debt, mainly concentrated in the real estate and construction sector and state-owned enterprises in general. The real estate and construction firms tend to face lower borrowing costs and could withstand a modest increase of interest rate shocks despite their high leverage. The corporate sector is however vulnerable to a significant slowdown in the real estate and construction sector. Our sensitivity analysis suggests that the share of debt that would be in financial distress would rise to about a quarter of total listed firm debt in the event of a 20 percent decline in real estate and construction profits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet